2011
DOI: 10.1111/j.1439-0531.2011.01809.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Boar Seminal Plasma on the Release of Prostaglandins and Interleukin‐6 by Porcine Endometrial and Cervical Cells and Bovine Endometrial Cells

Abstract: Artificial insemination (AI) of sows results in a significant elevation of prostaglandin F(2α) metabolite (PGFM) levels in peripheral plasma, whereas in mated sows such elevation is not seen. The aim of this study was to investigate whether boar seminal plasma (SP) has any effect on the release of PGFM, prostaglandin F(2α) (PGF(2α) ), prostaglandin E(2) (PGE(2) ) or interleukin-6 (IL-6) by in vitro cultured porcine endometrial (epithelial - pUE and stromal - pUS), cervical (pCE and pCS) and bovine endometrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 39 publications
(45 reference statements)
3
6
0
Order By: Relevance
“…The potent biological activity of boar seminal plasma to inhibit the release of prostaglandins and to stimulate IL-6 release by porcine endometrial, cervical and bovine endometrial cells has been demonstrated previously [1]. It is well known that prostaglandins F 2α and E 2 , which are of endometrial origin, regulate a number of important physiological functions during the estrous cycle and pregnancy in pigs [2,3].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…The potent biological activity of boar seminal plasma to inhibit the release of prostaglandins and to stimulate IL-6 release by porcine endometrial, cervical and bovine endometrial cells has been demonstrated previously [1]. It is well known that prostaglandins F 2α and E 2 , which are of endometrial origin, regulate a number of important physiological functions during the estrous cycle and pregnancy in pigs [2,3].…”
Section: Introductionmentioning
confidence: 88%
“…The cells were separated as described earlier [25][26][27][28] and recently modified by us [1]. Briefly, uterus and cervix were transported to the laboratory within 60 min after slaughter in ice-cold phosphate buffered saline (PBS), pH 7.4, saturated with O 2 :CO 2 (95%:5%) and supplemented with antibiotics.…”
Section: Isolation Culture and Cryopreservation Of Porcine Endometrimentioning
confidence: 99%
See 3 more Smart Citations